Faktor-faktor yang Berpengaruh Terhadap Harga Saham Subsektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia (BEI) - Nelsi Elta Sari; Sari Lestari Zainal Ridho; Afrizawati (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This research is to show the impact of EPS, and PBV on the share price. The samples of this reseach 14 companys from a population of 26 food and beverage company registered with IDX in 2016-2020. The method for determine the sample used is a purposive examination which is optional information contained on theÂ idx.co.idÂ site and to test the speculation used by the multiple linear regression tes, the classic assumption test inspection strategy, in particular autocorrelation test, t test and F test. The result of this examination is: (1) Earning Per Share (EPS) clearly affects the share price. Where the T test can be 7.681 which is greater than T tabel and (2) Price to Book Value (PBV) has a significant positive result on the Share Price. Where the t- count results show 8.167 and a significant 0,000.